Pembelajaran Integratif dan Hasil Belajar - Armizi Armizi (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2020)
Education plays an important role in the intellectual life of the nation, therefore from time to time efforts are always made to improve the quality of education. Improving the quality of education can be seen from the success in formal education in the form of student learning outcomes. Meanwhile, studentlearning outcomes are largely determined by the success of a teaching system. This means that the learning process is very decisive. This integrative learning is based on the view that learners or students build their own understanding of the topics they are studying rather than simply recording lessons in a systematically arranged form. This paper aims to make teachers understand the importance of being integrated in the learning process in order to increase good learning outcomes in learning